2016
DOI: 10.1002/esp.3895
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional flow structure and patterns of bed shear stress in an evolving compound meander bend

Abstract: Compound meander bends with multiple lobes of maximum curvature are common in actively evolving lowland rivers. Interaction among spatial patterns of mean flow, turbulence, bed morphology, bank failures and channel migration in compound bends is poorly understood. In this paper, acoustic Doppler current profiler (ADCP) measurements of the three‐dimensional (3D) flow velocities in a compound bend are examined to evaluate the influence of channel curvature and hydrologic variability on the structure of flow with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 67 publications
4
19
0
Order By: Relevance
“…This is true for both flood and ebb tides. The occurrence of the band is similar to the situation with a non-tidal meander reach [30,31].…”
Section: Bed Shear Stress Distributionsupporting
confidence: 68%
“…This is true for both flood and ebb tides. The occurrence of the band is similar to the situation with a non-tidal meander reach [30,31].…”
Section: Bed Shear Stress Distributionsupporting
confidence: 68%
“…Furthermore, a recent research study [18] of the turbulent flow in a 180 degree sharp open channel bend suggested that the maximum secondary flow strength occurred at the second half of the bend. There have been further studies over the last few years involving natural meandering channels [19][20][21][22][23]. However, a rectangular cross-section reduces the computational cost significantly compared to natural channels and, indeed, it is essential to gain inside in complex physics.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we estimate boundary shear stress using the Manning–Strickler law of bed resistance: τb=ρCfU2 where ρ is the fluid density and C f is the coefficient of friction computed using Cf=αr()Hks1/62 where H is the mean flow depth, α r is set as 8.1 (Parker, ), and k s is equal to 2.95 D 84 (here D 84 = 2.7 mm in September 2013 and 0.5 mm in October 2013 and July 2014) as specified by Whiting and Dietrich (). Equation can be generalized as a two‐dimensional vector with streamwise ( τ bu ) and cross‐stream ( τ bv ) component magnitudes of 0ptτbu=ρCfUU2+V2τbv=ρCfVU2+V2 where V is the depth‐averaged cross‐stream velocity following Engel and Rhoads ().…”
Section: Bifurcation Dynamicsmentioning
confidence: 99%